Illustrating the critical role of human dimensions research for understanding and managing recreational fisheries within a social-ecological system framework - Hunt, L. M.; Sutton, S. G.; Arlinghaus, R. (Fisheries management and ecology, 2013)
Effective management of recreational fishing requires understanding fishers and their actions. These actions constitute critical links between social and ecological systems that result in outcomes that feedback and influence recreational fishers' actions and the management of these actions. Although much research exists on recreational fishers and their actions, this research is often disconnected from management issues. One way to help to overcome this disconnect is to illustrate how past research on the social component of recreational fishing fits within an emerging coupled social‐ecological system (SES) framework. Herein, a conceptual SES is first developed with specific attention to recreational fisheries. This SES is then used to illustrate the importance of considering human dimensions research for articulating, studying and ultimately managing key outcomes of recreational fisheries (e.g. fish population conservation, fisher well‐being) using the example of harvest regulations and a brief review of past interdisciplinary research on recreational fishing. The article ends by identifying key research needs including understanding: how factors such as management rules affect the diversity of actions by recreational fishers; how governance and management approaches adapt to changing social and resource conditions; and how recreational fishers learn and share information.